Government Efforts In Disaster Emergency Capacity - Solechan Solechan (Administrative Law and Governance Journal, 2021)
AbstractIn this study, it will be explained about several matters relating to the actions of the government in its capacity as a body that has the authority as a supervisor, especially in the event of a disaster emergency. In this study regarding government oversight also has several objectives. Studies on disaster management are no longer considered to be the domination of the exact science of concentration, but rather to physical development as a means of disaster management. [1]On the other hand, the discussion this time has also spread or spread to other branches of social science such as sociology and anthropology. When we discuss aspects of disaster management from the perspective of social science it will be more inclined or lead to a behavioralism framework than an individual or someone in translating a disaster which later will also be a factor where the government can determine attitudes related to how to behave or take appropriate supervisory action. . The research method used is descriptive qualitative. Whereas information or supporting data will be taken from various sources both in legal factors and related journals and data collected by observing, documenting and searching for reliable sources.Keywords : Authority, authority, supervisor, disaster management.[1] Wasisto Raharjo Jati, "Analysis of Disaster Management Based on Cultural Theory Perspectives", Gadjah Mada University Journal of FISIPOL Department of Politics and Government, Volume 4 No. 4, June 2013.